Racialization of News: Constructing and Challenging Professional Journalism as "White Media". Issue 1 (February 2020) - Alamo-Pastrana, Carlos; Hoynes, William
This article explores the persistent racialization of professional journalism, describing the implicit processes that define "mainstream" news as white media. We emphasize the whiteness of U.S. news as emanating from cultural practices of professional journalism and institutional forces shaping the journalistic field rather than simply the demographic characteristics of the newsroom workforce. In theorizing how news has been constructed as white, we describe the historical foundations of the cultural authority of news and point to how such racialized authority has always been subject to enduring challenge. We analyze the complex cultural and political challenges that the Black press in the United States has long represented to the power of white media and racism; the Black press represents an alternative practice of journalism, one that critiques traditional notions of objectivity and situates news as a voice for equality and social justice. We close by discussing the newly resurgent white nationalist media and recent controversies surrounding prominent black female journalists as examples highlighting the structural limitations of white professional news media. Ultimately, we seek to understand the emergent racial dynamics of the journalistic field and how objectivity and white racial power are challenged and reaffirmed in our contemporary mediascape.